EXPLORING THE ROLE OF MUTED GROUP THEORY IN UNDERSTANDING WOMEN'S EXPERIENCES: A SYSTEMATIC LITERATURE REVIEW - Syawal, Marsaa Salsabila; Dwiandini, Afifah; Khaerunnisa, Divya Hangesty; Irwansyah, Irwansyah (International Journal of Humanity Studies (IJHS), 2024)
Muted Group Theory describes women as being viewed as a “muted” group because of male dominance. This paper aims to provide an overview of the gaps faced by women, to find out the application of the Muted Group Theory, and to identify the application of the basic concepts of the Muted Group Theory related to the experiences of women in their environment. This study uses the Systematic Literature Review (SLR) method. This research systematically identifies and evaluates women's experiences in several previous studies. However, along with the development of time and technology, communication not only focuses on direct interaction (face-to-face) but can also be carried out on other platforms such as social media or other online media. This can broaden women’s opportunities to express and share their opinions.